Disseminated rhinosporidial osteomyelitis: A rare case report - Samira Kumar Behera; Arpita Dhal; Ruchika Singh (Indian Journal of Pathology and Microbiology)
Rhinosporidiosis is a chronic granulomatous disease caused by Rhinosporidium seeberi, that affects mostly nasal and nasopharyngeal mucosa. Occurrence at extranasal sites such as cutaneous, subcutaneous, and bone is extremely rare. We hereby report a very rare case of disseminated rhinosporidial osteomyelitis.